2019
DOI: 10.3390/foods8060196
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polyphenolic Compounds in Cantaloupe Melon By-Products

Abstract: The Muskmelon (Cucumis melo L.), which includes several crops of great economic importance worldwide, belongs to the Cucurbitaceae family, and it is well recognized for culinary and medicinal purposes. The high fruit consumption produces a large quantity of waste materials, such as peels and seeds that are still rich in molecules like polyphenols, carotenoids, and other biologically active components that possess a positive influence on human health and wellness. A sustainable development in agro-food and agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 31 publications
2
38
2
1
Order By: Relevance
“…A volume of 5 μL was employed for the analysis on a Supelco Spherisorb ODS2 HPLC Column (250 × 4.6 mm), and the column was thermostatically controlled at 35 °C. The elution was conducted, as already reported [23], by employing 0.3% acetic acid solution (solvent A) and acetonitrile (solvent B). A gradient elution was performed as the following: the initial solvent was 90% A and 10% B; the gradient elution was changed from 10% to 20% B in a linear mode for 15 min; this composition was maintained at isocratic flow for 10 min; the solvent B reached 50% in 10 min and from 50 to 90% B in 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…A volume of 5 μL was employed for the analysis on a Supelco Spherisorb ODS2 HPLC Column (250 × 4.6 mm), and the column was thermostatically controlled at 35 °C. The elution was conducted, as already reported [23], by employing 0.3% acetic acid solution (solvent A) and acetonitrile (solvent B). A gradient elution was performed as the following: the initial solvent was 90% A and 10% B; the gradient elution was changed from 10% to 20% B in a linear mode for 15 min; this composition was maintained at isocratic flow for 10 min; the solvent B reached 50% in 10 min and from 50 to 90% B in 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Several other polyphenol-rich by-products are known, such as Cocoa shell, the waste of chocolate production, which contains catechin, epicatechin, and gallic acid [ 96 ]; the waste of black tea, which shows antioxidant and antimicrobial activity [ 97 ]; melon peels, which contain a great amount of polyphenols [ 98 ]; larch bark, a source of proanthocyanidin B7, a well-known antioxidant [ 99 ]; and maize bran containing ferulic acid [ 100 ].…”
Section: Polyphenolsmentioning
confidence: 99%
“…Melon is used as a tonic, laxative, galactagogue, diuretic, and diaphoretic, and its extract is known to exhibit high antioxidant activity, like superoxide dismutase [17,18]. Recent studies reported that the richest phytochemical was caffeic acid and that gallic acid, ellagic acid, catechin, ferulic acid, kaempferol, and chlorogenic acid were also the main phenolic compounds found in the extracts of melon peels and seeds [19,20]. Although water-soluble extracts of melon have positive effects on osteoblast differentiation [14], seminal evidence for their effects on osteoporosis is still inadequate.…”
Section: Introductionmentioning
confidence: 99%